A new species of Protopterna Meyrick, 1908 from Korea (Lepidoptera: Tortricidae, Tortricinae) - Jae-Cheon Sohn (SHILAP, 2023)
A new species of the genus Protopterna Meyrick, 1908, P. dongjooi Sohn, sp. nov. is described from Korea. The type series include one male and one female collected from Island Wando. The genus is recorded for the first time in Korea. The species represents the northernmost distribution of Protopterna. Photos of the habitus and genitalia of both sexes are provided.